Opera and drama in eighteenth-century London : the King's Theatre, Garrick and the business of performance - Woodfield, Ian (Cambridge studies in opera., 2001)
In this study, Ian Woodfield explores the cultural and commercial life of Italian opera in late eighteenth-century London. It was a period when theatre and opera worlds mixed, venues were shared, and agents and managers collaborated and competed. Through primary sources, many analysed for the first time, Woodfield examines such issues as finances, recruitment policy, the handling of singers and composers, links with Paris and Italy, and the role of women in opera management. These key topics are also placed within the context of a personal dispute between two of the most important managers of the day, the woman writer Frances Brooke and the actor David Garrick, which influenced the running of the major venues, the King's Theatre, Drury Lane and Covent Garden. Woodfield has also uncovered new information concerning the influential role of the eighteenth-century music historian and critic Charles Burney, as artistic advisor to the King's Theatre.--Publisher description.